การจัดสรรกำลังไฟฟ้าสูญเสียในระบบส่งสำหรับระบบการซื้อขายไฟฟ้าแบบผสม ระหว่างการซื้อขายผ่านตลาดกลางและการซื้อแบบคู่สัญญา - กานต์ วงษ์ปาน (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Nowadays, most power systems have been changed to an open market based structure, Under these new structures, there are three types of market models, a pool-based model, a bilateral-contract-based model and a hybrid model. When there is power transaction from generators to loads, it will cause power loss to the power system. This power loss costs a large amount of money per year. Thus, the fair and transparent loss allocation among participants has an important impact on the competitive environment. In the past, there were several researchers proposing the loss allocation methods for a power system. However, these methods could generally be applicable for only either pool-based market or bilateral contract-based market. This paper propose a new transmission loss allocation method for a mixed Pool and Bilateral market. The proposed method is based on a derivation of an actual loss formula. It applies the general concept that the transaction causing a larger amount of loss must be responsible for a greater amount of power losses. This proposed method has been tested with the 14-bus test system and IEEE-RTS 79 system. Satisfactory results have been obtained